Expression of human mammaglobin and clinicopathologic correlations in breast cancer: The findings in Malaysia - Fawwaz S Al-Joudi; Fahme A. K. Kaid; Ismarulyusda Ishak; Norhazilah Mohamed; Kairol Osman; Iskandar Zulkarnain Alias (Wolters Kluwer Medknow Publications, 2011)
Background: Human mammaglobin (hMAG) is a secreted protein which has been detected in breast epithelial cells of mammary glands and has been used as a specific marker for breast cancer. Objectives: This study aims at studying the hMAG expression and identifying the significant predictors of hMAG expression in breast cancer tissues. Materials and Methods: The tissue samples were obtained from two major teaching hospitals in the country. They were examined by immunohistochemistry (IHC) and the hMAG expression was evaluated using an established scoring system. Results: Out of 84 breast cancer tissue samples, hMAG was expressed in 50 samples (59.6%). The expression of hMAG was found to be increased with cancer grade. The output of logistic regression model showed that hMAG was overexpressed in breast cancer samples from the first hospital (P = 0.014), but not with those from the second hospital. Conclusions: It can be concluded that hMAG may serve in the diagnosis and the assessment of progression with the increased cancer grade. The dominance in hMAG expression in samples from HUSM may correlate with ethnic, environmental or genetic factors.